Characterization of concrete shrinkage induced strains in internally-restrained RC structures by distributed optical fiber sensing. (July 2021) - Bado, Mattia Francesco; Casas, Joan R.; Dey, Alinda; Berrocal, Carlos G.; Kaklauskas, Gintaris; Fernandez, Ignasi; Rempling, Rasmus
Abstract: The present paper reports the result of an inter-university experimental investigation on concrete shrinkage induced strains on embedded rebars instrumented with Distributed Optical Fiber Sensors (DOFS). The monitoring was performed for a standard 28 days drying time and for a shorter 6 days time span (reflecting realistic constructions schedules accelerations to meet set deadlines). The tested specimens were Reinforced Concrete (RC) tensile members differing in their geometry, DOFS employed and fiber/rebar bonding techniques. Regarding the latter, a combination of cyanoacrylate (for gluing) and silicone (protection) was found to be the optimal one for deployments inside RC structures. The DOFS-reported combined effect of concrete shrinkage and creep on the embedded rebars is compared with the Model Code 2010's predictions and employed to extract conclusions on the residual performance of the RC members at the end of their drying phase.